Oro facial digital syndrome type 2- An Indian case report - Naresh Bansal; Ashok Gupta; Manisha Goyal; Manish Sharma; Priyanshu Mathur; Manish Agarwal (Wolters Kluwer Medknow Publications, 2016)
The oral-facial-digital syndromes (OFDS) are rare genetic heterogenous group of disorders characterized by oral (mouth and teeth), facial and digital (fingers and toes) anomalies. OFDS are classified into 13 potential forms. OFDS Type II (Mohr syndrome) is an autosomal recessive disease characterized by oral (median cleft/pseudocleft lip, lobed tongue, high arched or cleft palate), facial (low nasal bridge with lateral displacement of inner canthi, broad nasal tip, retromicrognathia) and digital anomalies (clinodactyly, syndactly and polydactyly of hands and feet and duplication of thumb and hallux). This is the case report of an indian new born with OFDS type 2 manifestations.